(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The metaverse, an immersive virtual universe in which physical and digital realities converge, has emerged as a transformative pressure reshaping human interaction, era, and society. This review paper delves into the evolution of the metaverse, tracing its origins and pivotal tendencies